Apoptosis signaling associated with amyloid β-induced cellular dysfunction and degeneration : relevance for Alzheimer’s disease - Viana, Ricardo Jorge Soares, 1980- (2010)
Tese de Doutoramento em Farmácia (Bioquímica), Universidade de Lisboa, Faculdade de Farmácia, 2011